Karakteristik Mikrobiologi dan Orgaoleptik Air Mineral Dalam Kemasan (AMDK) Merek Khairunqu pada Kemasan Botol dengan Penggunaan Berbagai Cartridge Filter - Kamaluddin, Abdul Kadir; Mansur, Sukri; Rasulu, Hamidin (Universitas Khairun, 2024)
Drinking water is one of the most essential human need. As society advances and living standards rise, the amount of water available keeps growing. Purchasing clean water for domestic purposes, such drinking and bathing, must adhere to national and local laws as well as international standards (APHA and WHO). Determining consumer preference for Khairunqu Bottled Mineral Water (AMDK) goods and the degree of microbiological contamination present in bottled AMDK products are the two main objectives of this study. In compliance with SNI 3553:2015, cartridge filter type treatment was used in this study. A quantitative descriptive method is used in this study. This study investigated five different therapies. Using cartridge filters to create Khairunqu Bottled Mineral Water (AMDK) in bottles with organoleptic and microbiological characteristics is one of these methods. The findings indicate that the mineral water's organoleptic properties in Khairunqu bottles with different filter cartridges are as follows: color 5.63-5.87 (neutral), taste 5.71-6.0 (slightly), and odor 5.57-5.75 (neutral). The initial ALT temperature was 36°C ±2°C (1.0 x 101).Keywords: Bottled Mineral Water, Cartridge Filter